Summative assessment of clinical practice of student nurses: A review of the literature. (January 2016) - Helminen, Kristiina; Coco, Kirsi; Johnson, Martin; Turunen, Hannele; Tossavainen, Kerttu
Abstract: Objectives: To provide an overview of summative assessment of student nurses' practice currently in use. Design: Narrative review and synthesis of qualitative and quantitative studies. Data sources: With the support of an information specialist, the data were collected from scientific databases which included CINAHL, PubMed, Medic, ISI Web of Science, Cochrane library and ERIC published from January 2000 to May 2014. Sources used in all of the included studies were also reviewed. Review methods: 725 articles concerned with student nurse clinical practice assessment were identified. After inclusion and exclusion criteria, 23 articles were selected for critical review. Results: Findings suggest that the assessment process of student nurses' clinical practice lacks consistency. It is open to the subjective bias of the assessor, and the quality of assessment varies greatly. Student nurses' clinical assessment was divided into 3 themes: acts performed before final assessment, the actual final assessment situation and the acts after the final assessment situation. Mentors and students need teachers to provide them with an orientation to the assessment process and the paperwork. Terminology on evaluation forms is sometimes so difficult to grasp that the mentors did not understand what they mean. There is no consensus about written assignments' ability to describe the students' skills. Mentors have timing problems to ensure relevant assessment of student nurses. At the final interview students normally self-assess their performance; the mentor assesses by interview and by written assignments whether the student has achieved the criteria, and the role of the teacher is to support the mentor and the student in appropriate assessment. The variety of patient treatment environments in which student nurses perform their clinical practice periods is challenging also for the assessment of student nurses' expertise. Conclusions: Mentors want clinical practice to be a positive experience for student nurses and it might lead mentors to give higher grades than what student nurses in fact deserve. It is very rare that student nurses fail their clinical practice. If the student nurse does not achieve the clinical competencies they are allowed to have extra time in clinical areas until they will be assessed as competent. Further research needs to be carried out to have more knowledge about the final assessment in the end of clinical practice. Through further research it will be possible to have better methods for high quality assessment processes and feedback to student nurses. Quality in assessment improves patient safety.